2012
DOI: 10.1029/2011jd017290
|View full text |Cite
|
Sign up to set email alerts
|

Tree ring based precipitation reconstruction in the south slope of the middle Qilian Mountains, northeastern Tibetan Plateau, over the last millennium

Abstract: A tree ring (Sabina przewalskiiKom.) based millennial precipitation reconstruction on the south slope of the middle Qilian Mountains in the northeastern margin of Tibetan Plateau, China, was completed, which explains 48.5% of the variance in the instrumental precipitation from 1958 to 2004. The long‐term precipitation variation patterns were confirmed on the basis of the duration, magnitude, and intensify of the multidecadal dry (wet) events. There are several stronger multidecadal dry periods, 1092–1172, 1441… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 55 publications
(101 reference statements)
3
23
0
Order By: Relevance
“…It can be seen that positive correlations dominated for the latest 900 years and were statistically significant in the most recent 600 years (N Effective = 23 with critical r* = ±0.4133). This conformed with the findings by Sun and Liu (2012) relating droughts in the northeastern Tibetan Plateau to the solar minimums. The correlation was then reverted to negative (though not statistically significant) for most of the earlier periods (Fig.…”
Section: Relationships Between Moisture Conditions and Solar Activitysupporting
confidence: 76%
See 1 more Smart Citation
“…It can be seen that positive correlations dominated for the latest 900 years and were statistically significant in the most recent 600 years (N Effective = 23 with critical r* = ±0.4133). This conformed with the findings by Sun and Liu (2012) relating droughts in the northeastern Tibetan Plateau to the solar minimums. The correlation was then reverted to negative (though not statistically significant) for most of the earlier periods (Fig.…”
Section: Relationships Between Moisture Conditions and Solar Activitysupporting
confidence: 76%
“…Raspopov et al (2008) discovered the~200-year cycles in millennium-long tree ring data from Delingha and other sites in the mountains of Central Asia, but the cycles in the tree ring data had variable phase shifts with the 210-year de Vries solar cycle. More recently, based on a reconstructed millennium-long precipitation record in the Qilian Mountains to the north of our study region, Sun and Liu (2012) related periods of low precipitation to the solar minimums since 1063 CE. To investigate whether such relationships existed in our reconstructed series, we considered two datasets of solar activities: a 9300-year record of total solar irradiance (TSI) based on cosmogenic radionuclide 10Be production with a 5-year temporal resolution (as differences from the solar cycle minimum of 1366.57 W m −2 in 1986 in 40-year running means and resampled to 5-year intervals) (Steinhilber et al, 2009) and a 2001-year record of annual solar forcing estimated from multiple proxies (Crowley, 2000;Jones and Mann, 2004).…”
Section: Relationships Between Moisture Conditions and Solar Activitymentioning
confidence: 99%
“…7b) in our reconstruction are typically associated with El Niño-Southern Oscillation (ENSO) (Allan et al, 1996); similar periodicities have been identified in other temperature and precipitation reconstruction series in China (Fang et al, 2009;Li et al, 2011a;Y. Zhang et al, 2011;Sun and Liu, 2012;Deng et al, 2013). The instrumental data-based research into ENSO and temperature in the Qilian Mountains showed that surface temperatures tend to increase during the El Niño years, while they tend to decreased during the La Niña events in this area (Lan et al, 2003;C.…”
Section: The Periodicity Of the Reconstruction And The Possible Forcimentioning
confidence: 87%
“…Sun et al (2002) found the EASM region to be not only under the effect of zonal but also meridional land-sea thermal difference. Sun et al (2000) defined an index of land-sea thermal difference (ILSTD) that includes zonal and meridional land-sea thermal difference.…”
Section: The Index Of Land-sea Thermal Differencementioning
confidence: 99%
“…On the basis of reconstructions of precipitation variability over large-scale monsoon Asia, together with reconstructions of monsoon variability, it appears that four out of five episodes of "monsoon megadroughts" during the Little Ice Age (LIA) occurred over monsoon Asia within a period of generally reduced monsoon strength between AD 1300 and 1700 (Sinha et al, 2011). Several candidate forcing factors that are important and potentially independent mechanisms for monsoon failures have been linked to the occurrence of droughts over eastern China, including solar activity (Zhang and Liang, 2010;Sun and Liu, 2012), volcanic eruptions (Xu, 1986;Shen et al, 2007;Peng et al, 2009b;Zhang and Liang, 2010;Zhang et al, 2013), anomalous sea surface temperature such as the one associated with ENSO (e.g., Huang and Wu, 1989;Liu and Ding, 1992;Zhang and Xue, 1994;Lau and Weng, 2000;Li et al, 2005Li et al, , 2010Shen et al, 2007) and Pacific Decadal Oscillation (PDO, e.g., Zhu and Yang, 2003;Shen et al, 2006), and anomalous sea level pressure such as North Atlantic Oscillation (NAO, e.g., Sung et al, 2006;Yang et al, 2012;Barriopedro et al, 2012). A great deal of work has been carried out on drought events, but the possible mechanism remains unclear because of the complex climate system in eastern China.…”
Section: Introductionmentioning
confidence: 99%